What Drives Differences in Management Practices? - Bloom, Nicholas; Brynjolfsson, Erik; Foster, Lucia; Jarmin, Ron; Patnaik, Megha; Saporta-Eksten, Itay; Van Reenen, John (The American economic review, 2019)
Partnering with the US Census Bureau, we implement a new survey of “structured” management practices in two waves of 35,000 manufacturing plants in 2010 and 2015. We find an enormous dispersion of management practices across plants, with 40 percent of this variation across plants within the same firm. Management practices account for more than 20 percent of the variation in productivity, a similar, or greater, percentage as that accounted for by R&D, ICT, or human capital. We find evidence of two key drivers to improve management. The business environment, as measured by right-to-work laws, boosts incentive management practices. Learning spillovers, as measured by the arrival of large “Million Dollar Plants” in the county, increases the management scores of incumbents.